2020
DOI: 10.3389/fpls.2020.00038
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Brassinolide Alleviates Salt Stress in Malus hupehensis Rehd. by Regulating the Transcription of NHX-Type Na+(K+)/H+ Antiporters

Abstract: Brassinolide (BL) mediates various physiological processes and improves plant tolerance to abiotic stresses. However, the effects and mechanism of exogenous BL on the salt tolerance of apple seedlings remain unclear. Herein, we investigated the role of BL in the salt stress response of Malus hupehensis Rehd., a widely grown apple rootstock. Saltstressed apple seedlings showed significant decline in chlorophyll content and photosynthetic rate, and the application of 0.2 mg/L exogenous BL alleviated salt stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 65 publications
2
58
0
Order By: Relevance
“…The initial cloning and overexpression of AtNHX1 in Arabidopsis firmly demonstrated its important role in salinity stress tolerance ( Apse et al., 1999 ), and many additional studies subsequently confirmed that NHX overexpression lead to improved salt tolerance in diverse species ( Zhang and Blumwald, 2001 ; Ohta et al., 2002 ; Rodriguez-Rosales et al., 2008 ). NHX transcript levels are induced by salt in both leaf ( Quintero et al., 2000 ; Venema et al., 2003 ; Kagami and Suzuki, 2005 ; Li et al., 2018 ; Sun et al., 2019 ; Su et al., 2020 ) and roots ( Fukuda et al., 2004a ; Fukuda et al., 2004b ; Zörb et al., 2004 ; Ye et al., 2009 ; Zhang et al., 2018 ). A similar increase was reported upon plant exposure to dehydration ( Li et al., 2006 ), hyperosmotic stress ( Fukuda et al., 2004a ; Fukuda et al., 2004b Yokoi et al., 2002 ), or ABA treatment ( Yokoi et al., 2002 ; Venema et al., 2003 ).…”
Section: Cpa1 Superfamilymentioning
confidence: 99%
“…The initial cloning and overexpression of AtNHX1 in Arabidopsis firmly demonstrated its important role in salinity stress tolerance ( Apse et al., 1999 ), and many additional studies subsequently confirmed that NHX overexpression lead to improved salt tolerance in diverse species ( Zhang and Blumwald, 2001 ; Ohta et al., 2002 ; Rodriguez-Rosales et al., 2008 ). NHX transcript levels are induced by salt in both leaf ( Quintero et al., 2000 ; Venema et al., 2003 ; Kagami and Suzuki, 2005 ; Li et al., 2018 ; Sun et al., 2019 ; Su et al., 2020 ) and roots ( Fukuda et al., 2004a ; Fukuda et al., 2004b ; Zörb et al., 2004 ; Ye et al., 2009 ; Zhang et al., 2018 ). A similar increase was reported upon plant exposure to dehydration ( Li et al., 2006 ), hyperosmotic stress ( Fukuda et al., 2004a ; Fukuda et al., 2004b Yokoi et al., 2002 ), or ABA treatment ( Yokoi et al., 2002 ; Venema et al., 2003 ).…”
Section: Cpa1 Superfamilymentioning
confidence: 99%
“…Four PPKLs were characterized in A. thaliana: BSU1, BSL1, BSL2, and BSL3 [55][56][57], which showed a functional relevance in interactively affecting brassinosteroid signaling [54]. Brassinosteroid signaling was found to mediate plant development and adaptation under salt stress [56,58]. An SNP located on chromosome 3 (S3_3511428) annotated as BSL2 was significantly associated germination rate at the 9-day seedling stage (Table 4, Figure 3), although no direct evidence showed that the increased activity of BSL2 was triggered by salt stress.…”
Section: Gwas Analysis Of Seedling Germination Traits Under Salt Stressmentioning
confidence: 99%
“…Plant growth regulators usually affect plant growth and development in a dose-dependent manner. Su et al (Su et al 2020). reported that the effect of applying 0.2 mg/L of BL on improving the salt tolerance of apple seedlings is much better than the effect of applying BL concentrations of 0.05 and 1.0 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the kilndried samples were digested with 12 mL of HNO 3 and HClO 4 and diluted with deionized H 2 O to 25 mL. Elemental analysis of Fe was performed via inductively coupled plasma-optical emission spectrometry (PerkinElmer, Waltham Massachusetts, USA) as described by Su et al (Su et al 2020). Each experiment was independently repeated three times.…”
Section: Determination Of Fe Contentmentioning
confidence: 99%